Relational Self‐Construal as a Moderator of Social Support in Career Decision Making. Issue 1 (March 2017) - Li, Yaoshan I.; Hazler, Richard J.; Trusty, Jerry
Abstract : The authors examined relational self‐construal as a moderator of the influence of social support on career decision‐making difficulties among 352 college students (65% women, 63% Caucasian). Results of hierarchical regression analyses supported the hypothesis that individuals with higher relational self‐construal reported fewer difficulties in terms of lack of information and inconsistent information in career decision making as social support increased. Social support, however, did not reduce career decision‐making difficulties for those with lower relational self‐construal. Relational self‐construal did not moderate the relationship between social support and lack of readiness in career decision‐making difficulties as expected, possibly because of conceptual and measurement issues. Results suggest counselors work from relational and contextual perspectives to foster clients' self‐views and to use social support to facilitate their career decision making.